2009
DOI: 10.1254/jphs.08262fp
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin-Induced Glutamate Release Is Implicated in Nociceptive Processing Through Activation of Ionotropic Glutamate Receptors and Group I Metabotropic Glutamate Receptor in Primary Afferent Fibers

Abstract: Abstract. Glutamate (Glu) is the major excitatory neurotransmitter in the central nervous system. The role of peripheral Glu and Glu receptors (GluRs) in nociceptive transmission is, however, still unclear. In the present study, we examined Glu levels released in the subcutaneous perfusate of the rat hind instep using a microdialysis catheter and the thermal withdrawal latency using the Plantar Test following injection of drugs associated with GluRs with / without capsaicin into the hindpaw. The injection of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 33 publications
(29 reference statements)
2
44
0
Order By: Relevance
“…An analogous result was observed when nociceptor fiber discharge during a brief heat stimulus was not attenuated by APDC, but the discharge generated by the longer-lasting algogen capsaicin was reduced [6]. The release of glutamate into the skin by keratinocytes [19] or reflex activation of the peripheral terminals of primary afferent fibers [25; 30] under injury or inflammatory conditions could produce endogenous activation of group II mGluRs leading to negative feedback and inhibition of the ongoing response. This schema is consistent with the presynaptic inhibitory effect of group II mGluRs reported in other parts of the nervous system [42], with the receptive peripheral ending from these pseudo-unipolar axons functioning analogously to a presynaptic terminal.…”
Section: Discussionmentioning
confidence: 85%
“…An analogous result was observed when nociceptor fiber discharge during a brief heat stimulus was not attenuated by APDC, but the discharge generated by the longer-lasting algogen capsaicin was reduced [6]. The release of glutamate into the skin by keratinocytes [19] or reflex activation of the peripheral terminals of primary afferent fibers [25; 30] under injury or inflammatory conditions could produce endogenous activation of group II mGluRs leading to negative feedback and inhibition of the ongoing response. This schema is consistent with the presynaptic inhibitory effect of group II mGluRs reported in other parts of the nervous system [42], with the receptive peripheral ending from these pseudo-unipolar axons functioning analogously to a presynaptic terminal.…”
Section: Discussionmentioning
confidence: 85%
“…For instance, it has been reported that knocking down mGluR1 in rat lumbar spinal cord could reduce hyperalgesia dramatically (31). Moreover, mGluR1 antagonists MPEP and 7-(hydroxyimino) cyclopropa[ b ]chromen-1 a-carboxylate ethyl ester (CPCCOEt) proved successful in blocking capsaicin-induced glutamate release, indicating that mGluR1 activation may influence nociception through modulation of glutamate release (32). Recent evidences demonstrated that application of a group I mGluR selective agonist (DHPG) on DRG neurons could cause a significant increase in inward calcium currents (9), which could enhance the release of glutamate from neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Intraplantar injection of L-glutamate or iGluR agonists into the hindpaw evokes thermal and mechanical hyperalgesia and allodynia, which can be blocked by appropriate antagonists [7, 1012]. …”
Section: Introductionmentioning
confidence: 99%
“…A broad range of stimuli such as noxious heat, protons, lipid-derived endovanilloids, and inflammatory mediators either directly activate or modulate TRPV1 [13, 14], and stimulation of TRPV1 elicits the release of glutamate [12, 15, 16]. At the peripheral terminals of primary afferents, TRPV1-mediated Ca 2+ influx triggers the release of neuropeptides and neurotransmitters, which is responsible for nociceptive processing [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation